Efficacy and safety comparison of combination of 0.04% tretinoin microspheres plus 1% clindamycin versus their monotherapy in patients with acne vulgaris: a phase 3, randomized, double-blind study. (17th November 2021) - Dogra, S.; Sumathy, T. K.; Nayak, C.; Ravichandran, G.; Vaidya, P. P.; Mehta, S.; Mittal, R.; Mane, A.; Charugulla, S. N.
Abstract: Background and objectives: There is an unmet need for topical treatments with good tolerability in management of acne vulgaris. The present study aimed to evaluate efficacy and safety of a novel tretinoin (microsphere, 0.04%) formulation in combination with clindamycin (1%) gel for treatment of acne vulgaris. Materials and methods: This phase 3 randomized, double-blind study included patients with moderate-to-severe acne. Patients were treated with tretinoin (microsphere, 0.04%) + clindamycin (1%) or one of the monotherapies (tretinoin, 0.025%; clindamycin, 1%). Key endpoints included percent change in lesion counts, and improvement in Investigator's Static Global Assessment (ISGA) score. Results: 750 patients were randomized (combination, n = 300; tretinoin and clindamycin, each n = 150). At week 12, reductions in inflammatory (77%), non-inflammatory (71%) and total lesions (73%) were significantly greater with combination treatment versus either monotherapy ( p < .03). Proportion of patients rated 'clear' or 'almost clear' with ≥2-grade ISGA improvement was higher with combination (46%) versus monotherapies ( p < .02). Adverse events occurred in 20 patients, most were mild-moderate; no deaths or serious adverse events were reported. The discontinuation rates due to adverse events with combination therapy were low (≤1%). Conclusion: The once-daily, microsphere-based formulation was generally tolerable with a positive impact on therapeutic outcomes and patients' compliance. ClinicalTrial Registration No: CTRI/2014/08/004830